The Effect of Heuristic Bias on Investment Decisions in The Indonesia Stock Exchange During the Covid-19 Pandemic - Muthia Siti Khoirunnisa; Sulaeman Rahman; Kurniawan Saefullah (Budapest International Research and Critics University, 2022)
This study aims to determine the effect of heuristic bias on investment decisions on the Indonesia Stock Exchange during the Covid-19 Pandemic. The third bias is the main bias in decision making under conditions of uncertainty. Behavioral finance research on heuristics is still very limited in developing countries, especially in Indonesia. The method used in this research is descriptive and verification. This study uses a quantitative approach with primary data sources. The population in this study is 8,103,795 people who are investors who already have shares in the IDX. The sampling technique used purposive sampling with a total sample of 240 respondents. Data collection techniques through questionnaires distributed online (google form). The data analysis technique used Structural Equation Modeling – Partial Least Square.